Bienestar psicológico en la clase de educación física en escolares / Psychological well-being in the physical education class in schoolchildren - Jayson Andrey-Bernate; Ingrid Patricia Fonseca-Franco; Kevin Gaviria-Ramírez; Wilson David Pulido-Cabrera; Iván Camilo Sánchez-Alvis; Alexander Guataquira-Romero (Universidad de Camagüey Ignacio Agramonte Loynaz, 2020)
The objective of this article is to analyze the levels of psychological well-being presented in school students in physical education class, for this the questionnaire of the scales of psychological well-being proposed by Ryff in 1989 was applied and was adapted by Van Dierendonck in 2004 The incidental sample was made up of 210 students. The methodology is descriptive quantitative in nature with a cross-sectional approach, the main finding is that they are not fully satisfied in the 6 dimensions and as the main conclusion is that physical education classes in school institutions can be associated towards the improvement of physical health and mental providing various benefits.